One-dimensional model of a closed low-pressure adsorber for thermal energy storage. (February 2018) - Schaefer, M.; Thess, A.
Highlights: One-dimensional model for closed low-pressure zeolite honeycomb adsorber. Rarefaction effects and convective heat transport by the vapour are included. Heat and mass transfer over a broad range of parameters is studied. Process is mainly limited by heat transport and limited by adsorption in few cases. Abstract: The energy transition from fossil to renewable energy requires the development and integration of efficient energy storages. For thermal energy storage, concepts based on adsorption are promising. One key challenge is to overcome limitations of the storage performance by the heat and mass transfer. Against this background, a closed low-pressure adsorber with zeolite 13X honeycomb adsorbent is studied numerically to identify the limiting factors. The focus of the study is on the adsorption process with the heat extraction limited to the end of the zeolite honeycomb arrangement. A detailed model which takes effects of rarefied gas flow (e.g. slip) as well as cooling effects by the inflowing vapour into account is derived. The model is applied to study the mass transport, heat transport and adsorption over a broad range of relevant geometry and process parameters. The simulations demonstrate that the adsorption process is not limited by the mass transport and isobaric conditions can be assumed in most of the studied cases. In addition, special effects of rarefied gas flow are found to be negligible. Regarding the heat transport, the convective cooling by the vapour is found only to be significant for a very short initial time period. Further analysis show that the process is mainly limited by the heat transport. Only for short channels and wide channel diameters the process becomes limited by the adsorption.